BOOSTING EMPLOYEE PERFORMANCE THROUGH EMPOWERING LEADERSHIP: MANAGING INFORMATION OVERLOAD AND SOCIAL MEDIA FATIGUE - Arlina Melianita; Ervin Nora Susanti; Herni Widiyah Nasrul (RADJA PUBLIKA, 2026)
This study examines the role of empowering leadership in improving employee performance within digitally connected workplaces characterized by information overload and social media fatigue. The research explores how excessive digital communication, continuous information exposure, and social media usage influence employee well-being, psychological exhaustion, and workplace productivity. Using a qualitative research approach, data were collected through semi-structured interviews with employees and managers working in digitally intensive organizational environments. The findings indicate that information overload and social media fatigue negatively affect employee concentration, engagement, and overall work performance. However, empowering leadership practices such as employee autonomy, participation, trust, and supportive communication help reduce the negative impact of digital workplace stressors and improve employee adaptability and motivation. The study further demonstrates that empowering leadership functions as an important organizational resource that enhances employee well-being and supports sustainable performance in highly connected work environments. The findings contribute to empowering leadership literature and digital workplace research by integrating leadership theory with contemporary issues related to digital stress and employee productivity. Practically, the study offers recommendations for organizations to implement supportive leadership practices, effective digital communication management strategies, and employee well-being programs to maintain productivity and organizational effectiveness in modern workplaces.